2005
DOI: 10.1128/jcm.43.6.2741-2749.2005
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Genetic Diversity of Haemophilus influenzae Serotype b (Hib) Strains after Introduction of Hib Vaccination in The Netherlands

Abstract: Recently, there has been an increase in The Netherlands in the number of cases of invasive disease caused by Haemophilus influenzae serotype b (Hib). To study a possible change in the Hib population that could explain the rise in incidence, a multiple-locus variable number tandem repeats analysis (MLVA) was developed to genotype H. influenzae isolates. The MLVA enabled the differentiation of H. influenzae serotype b strains with higher discriminatory power than multilocus sequence typing (MLST). MLVA profiles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 34 publications
3
35
1
1
Order By: Relevance
“…This technique, used in the present study, revealed six STs previously described and four new STs among the Polish encapsulated H. influenzae isolates tested. The most prevalent ST among the Hib isolates was ST6, which had been previously observed in the United States, Norway, Russia, The Netherlands, and the Czech Republic (www.mlst.net) (15,18,27). In the last country, 22 out of the 26 Hib isolates tested belonged to the ST6 (15).…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…This technique, used in the present study, revealed six STs previously described and four new STs among the Polish encapsulated H. influenzae isolates tested. The most prevalent ST among the Hib isolates was ST6, which had been previously observed in the United States, Norway, Russia, The Netherlands, and the Czech Republic (www.mlst.net) (15,18,27). In the last country, 22 out of the 26 Hib isolates tested belonged to the ST6 (15).…”
Section: Discussionmentioning
confidence: 62%
“…This fact is especially well known for Hib isolates, which are genetically homogenous and which the relationship has been found even for isolates originating from different countries and from different decades (18,21,32). However, in The Netherlands an increase in the genetic diversity of the Hib population after the introduction of vaccination against Hib has been reported recently (27).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Subsequent MLST of N. meningitidis yielded 47 sequence types (STs) from 92 strains (128), and for M. catarrhalis, 173 MLST STs were observed among 268 isolates (153). In contrast, MLST of H. influenzae serotype b, considered to be monomorphic (clonal), yielded 29 STs from 241 strains (129). These results indicate that the M. catarrhalis species comprises a panmictic population of isolates, although serosensitive lineage isolates appear to be more clonal than the seroresistant lineage (153).…”
Section: Heterogeneity Of the M Catarrhalis Speciesmentioning
confidence: 99%